2021
DOI: 10.3390/nu13103667
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Is Enough to Provoke Deleterious Effects in Descendants of Fructose-Fed Mothers and Their Fetuses

Abstract: The role of fructose in the global obesity and metabolic syndrome epidemic is widely recognized. However, its consumption is allowed during pregnancy. We have previously demonstrated that maternal fructose intake in rats induces detrimental effects in fetuses. However, these effects only appeared in adult descendants after a re-exposure to fructose. Pregnancy is a physiological state that leads to profound changes in metabolism and hormone response. Therefore, we wanted to establish if pregnancy in the progeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…Several experimental models have evaluated the effects of maternal high fructose consumption, alone or in combination with a high sodium and/or high fat diet, or with different doses of fructose (usually very high doses) ( Olatunji et al, 2001 ; Abdulla et al, 2011 ; Tain et al, 2015a ; Rodrigo et al, 2016 ; Saad et al, 2016 ; Fauste et al, 2021 ); however, few have evaluated in detail the effects on the structural and functional alterations of the kidneys from the offspring of rats subjected only to fructose overload.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental models have evaluated the effects of maternal high fructose consumption, alone or in combination with a high sodium and/or high fat diet, or with different doses of fructose (usually very high doses) ( Olatunji et al, 2001 ; Abdulla et al, 2011 ; Tain et al, 2015a ; Rodrigo et al, 2016 ; Saad et al, 2016 ; Fauste et al, 2021 ); however, few have evaluated in detail the effects on the structural and functional alterations of the kidneys from the offspring of rats subjected only to fructose overload.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we demonstrate that maternal fructose intake produces changes in female descendants that alter their own pregnancy, leading to deleterious effects in their fetuses [ 27 ]. Since we found that fructose intake during pregnancy can directly affect the enzymatic production of H 2 S in placenta ( Figure 2 B,E), we were interested to know if maternal fructose intake can also induce epigenetic changes that would affect placental production of H 2 S in the offspring through a fetal programming mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described that maternal fructose intake produces changes in female progeny that alter their own pregnancy, such as lipid accretion in the placenta [ 27 ]. However, in the present study we have found that maternal fructose consumption induces placental H 2 S synthesis in the offspring, when they are pregnant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations